The effect of prophylactic ankle bracing on physical performance measures in jumping athletes - Henderson, Z.; Sanzo, P.; Zerpa, C. (International Journal of Sports Science, 2016)
Introduction and Objective: Prophylactic bracing of the ankle is commonly used in jumping sports in an effort to reduce the risk of injury; however, the research surrounding the effectiveness of ankle braces at reducing the risk of injury is far from conclusive. While there may be some merit to wearing an ankle brace prophylactically to reduce the risk of injury, the potential impact on game and physical performance, such as vertical jumping and agility has not been well studied. Therefore, the purpose of this study was to examine the effect of two common ankle orthosis (ASO EVO©, Active Ankle T1©) on vertical jump height and agility time in varsity jumping sport athletes. Methods: Fourteen participants (6 male, 8 female; 6 basketball, 8 volleyball) with a mean age of 20.92+/-1.94 years had their vertical jump height and agility time assessed on three separate days under one of three conditions (no brace, ASO EVO© Brace, or Active Ankle T1© Brace) on both ankles each day. The independent variable in this study was brace type for each condition and the dependent variables were vertical jump height and time to complete agility test. A one-way repeated measures ANOVA was used to examine the effect of brace type on vertical jump height and time to complete agility test with an alpha level set at pResults: Descriptive statistics showed that vertical jump height was reduced when wearing the ASO EVO© Brace (M=276.66, SD=20.28) and Active Ankle T1© Brace (M=275.79, SD=18.67) when compared to the no brace control condition (M=278.14, SD=18.43). Inferential statistics revealed a significant reduction in jump height when wearing an ankle brace, F(1.66, 21.63) = 4.175, p = 0.035. Post-hoc analysis revealed that the significant difference was between the mean jump height of the no brace control condition and the Active Ankle T1© Brace (p=0.01). No significant difference, however, was found between ankle brace conditions with respect to agility test times. Conclusions: These findings suggest that ankle bracing may have a negative impact on vertical jump height, regardless of the type of brace worn. A decrease in vertical jump was more evident when wearing the Active Ankle T1© Brace compared to the ASO EVO© Brace. This reduction resulted in a 2.35 cm decrease in vertical jump height on average. With respect to agility, overall agility time was not affected by wearing an ankle brace. However, given the lack of significant evidence to support ankle bracing`s ability to reduce the risk of injury, the potential for ankle orthosis to decrease physical performance should be considered by athletes, healthcare providers, coaches, and teams using prophylactic ankle bracing in an effort prevent injury.